Paper 04: The Effects of Glenohumeral Osteoarthritis on Early Clinical Outcomes Following Arthroscopic Rotator Cuff Repair. Issue 5 (31st May 2022) - Lam, Patrick; Hackett, Lisa; Murrell, George AC; Yeo, Wai Weng
Objectives: It is unclear if concomitant glenohumeral osteoarthritis is protective or detrimental with respect to rotator cuff integrity after arthroscopic repair surgery. We hypothesized that the associated stiffness might protect the repaired tendon. In the alternate, arthritis might reflect a gradual degeneration of the joint including a degenerative tendon and therefore predispose the repair to re-tear. Therefore, the purpose of this study was to investigate whether concomitant osteoarthritic changes found intra-operatively during arthroscopic rotator cuff repairs (RCR) have a beneficial or detrimental effect on post-operative repair integrity. Methods: This study is a post-hoc analysis of prospectively collected data of patients who underwent primary arthroscopic RCR between 2005 and 2019 by a single surgeon. Patients were divided into an osteoarthritic group and a control group based on the presence or absence of intra- operative osteoarthritic changes respectively. The primary outcome measure was cuff integrity detected by post-operative ultrasound at 6-months. The secondary outcomes were patient-reported outcomes including shoulder pain, stiffness, level of activity at work and level of sport, and physician-reported outcomes including shoulder range of motion and strength. Results: A total of 2155 consecutive patients met the inclusion criteria with a mean age of 59 years (SD=0.2) and there were more males as compared to females (56% vs. 44%). 28% of patients undergoing RCR had osteoarthritic changes detected intra- operatively. Intra-operatively, the osteoarthritic group had more full-thickness tears (64% vs. 59%) (p<.001), a larger mean anteroposterior tear length [20mm (SD=0.5) vs. 17mm (SD=0.4)] (p<.001) and a larger mean mediolateral tear length [17mm (SD=0.5) vs. 15mm (SD=0.4)] (p<.001). Ultrasonographic evaluation at 6-months post-surgery demonstrated that the osteoarthritic group had a higher incidence of cuff re-tear rate as compared to the control group (15% vs. 11%) (p=.016) ( Figure 1 ). However, after performing a multiple logistic regression analysis, osteoarthritis was not found to be an independent predictor of re-tear. There were very marginal differences in patient-reported outcomes at 6-months after surgery between the two groups ( Table 1 ). The osteoarthritic group reported lesser post-operative frequency of activity pain [2.0 (SD=1.46) vs. 2.2 (SD=1.43)] (p=.005), frequency of extreme pain [0.8 (SD=1.35) vs. 1.0 (SD=1.41)] (p=.035) and level of pain during overhead activity [1.7 (SD=1.30) vs. 1.9 (SD=1.30)] (p=.021) as compared to controls. As compared to controls, the osteoarthritic group also experienced lesser post-operative stiffness [1.5 (SD=1.32) vs. 1.6 (SD=1.31)] (p=.019) and reported lower intensities of work-related activities [1.1 (SD=0.88) vs. 1.2 (SD=0.85)] (p=.038) and lower level of sport activity [0.4 (SD=0.62) vs. 0.5 (SD=0.70)] (p=.004). In terms of physical examination at 6-months following surgery ( Table 2 ), the osteoarthritic group were found to have lesser range of motion in forward flexion [146° (SD=33.1) vs. 151° (SD=31.2)] (p=.009), abduction [127° (SD=38.8) vs. 131° (SD=38.1)] (p=.034), external rotation [50° (SD=21.4) vs. 52° (SD=21.0)] (p=.024) and internal rotation (L1 vertebrae (SD=4.2) vs. T12 vertebrae (SD=4.2)] (p=.004) as compared to controls. The osteoarthritic group as weaker internal rotation strength [68N (SD=30.5) vs. 73N (SD=32.9)] (p=.004), external rotation strength [57N (SD=25.3) vs. 60N (SD=27.2)] (p=.026), supraspinatus flexion strength [45N (SD=26.8) vs. 50N (SD=27.9)] (p<.001), lift-off [40N (SD=24.3) vs. 44N (SD=25.3)] (p<.001) and adduction strength [76N (SD=36.5) vs. 81N (SD=39.3)] (p=.008) as compared to the control group. Conclusions: Patients with concomitant glenohumeral osteoarthritis who underwent arthroscopic RCR had higher re-tear rates at 6-months after surgery. However, osteoarthritis is not an independent predictor of rotator cuff re-tear at 6-months. Therefore, arthroscopic RCR is a viable surgical option for these patients. Figure 1: Proportion of intract vs. torn rotator cuff repairs between the osteoarthritic group (n=1552) and control group (n=603) at 6-months post-operative follow-up (p=.016). Table 1: 6-month post-operative pain scares and shoulder function in the osteoarthritic group vs. control group. Table 2: 6-month post-operative shoulder range of motion and strength in the osteoarthritic group vs. control group.